Intravenous captopril treatment in patients with severe cardiac failure. Issue 2 (February 1986) - Rademaker, M; Shaw, T R; Williams, B C; Duncan, F M; Corrie, J; Eglen, A; Edwards, C R
Abstract : The effect of intravenous captopril was studied in 26 patients with severe chronic heart failure. Fourteen patients received a 25 mg intravenous bolus dose and 12 patients were given a series of incremental intravenous doses over the range 0.3125-45 mg. After the 25 mg bolus dose there was a rapid reduction in systemic vascular resistance and systemic blood pressure. The effect was greatest five minutes after the dose when cardiac output was increased by 20%. Mean right atrial pressure and pulmonary end diastolic pressure fell more slowly and reached their nadir 60 minutes after administration. Plasma free captopril concentration was significantly correlated with percentage reduction in systemic vascular resistance 15 minutes after the bolus injection, but was not correlated with either changes in right atrial or pulmonary artery pressures. With the series of incremental doses there was a progressive fall in systemic vascular resistance until a cumulative dose of 5.0 mg was reached; beyond this there was no further significant change. The rapid response to intravenous captopril indicates that it may be useful in the treatment of patients with severe heart failure who require intensive treatment. After intravenous injection of captopril haemodynamic responses in patients with heart failure were greatest at plasma concentrations of 100 g/ml to 150 ng/ml. This is considerably higher than the plasma free captopril concentrations found after conventional oral doses of captopril.